2003
DOI: 10.1034/j.1600-0625.12.s2.1.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanosome transfer to and translocation in the keratinocyte

Abstract: Complexion coloration in humans is primarily regulated by the amount and type of melanin synthesized by the epidermal melanocyte. However, additional and equally contributing factors consist of (1) efficient transfer of melanin from the melanocytes to the neighboring keratinocytes and (2) distribution and degradation of the transferred melanosomes by the recipient keratinocytes. Once synthesized in the cell body of the epidermal melanocyte, pigmented melanosomes are translocated down the dendrites and captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
204
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(209 citation statements)
references
References 51 publications
4
204
0
1
Order By: Relevance
“…Tem sido sugerido que o pigmento, no interior destas células atua, também, como varredor de radicais livres fotoproduzidos, sempre no sentido de proteger o DNA celular. 12,22,23 As propriedades de fotoproteção da melanina, na pele humana, têm sido bem documentadas e ocorrem pela absorção e dispersão, tanto da luz ultravioleta quanto da luz visível. Essa absorção aumenta linearmente na faixa de 720-620 nm e então, exponencialmente, através de ondas mais curtas (300-600 nm).…”
Section: Melaninaunclassified
“…Tem sido sugerido que o pigmento, no interior destas células atua, também, como varredor de radicais livres fotoproduzidos, sempre no sentido de proteger o DNA celular. 12,22,23 As propriedades de fotoproteção da melanina, na pele humana, têm sido bem documentadas e ocorrem pela absorção e dispersão, tanto da luz ultravioleta quanto da luz visível. Essa absorção aumenta linearmente na faixa de 720-620 nm e então, exponencialmente, através de ondas mais curtas (300-600 nm).…”
Section: Melaninaunclassified
“…In response to hormones and UV irradiation, melanin pigments are synthesized in melanosomes, which are transferred from the tips of melanocyte dendrites to the surrounding keratinocytes to protect against UV damage or carcinogenic effects (Boissy 2003;Okazaki et al 1976;Seiberg 2001). Studies have demonstrated that the dendritic outgrowth of melanocyte/melanoma cells is promoted by UV irradiation, cAMP-elevating agents and growth factors, as well as by the induction of melanogenesis; therefore, dendrites are recognized as a morphological indicator of melanocyte/melanoma cell differentiation (Hara et al 1995;Yoshida et al 2000).…”
Section: Dendrite Formationmentioning
confidence: 99%
“…Melanin is synthesized in melanosomes, and transferred from melanocytes to keratinocytes [1] . Melanin production is mainly controlled by the expression and activity of tyrosinase, which is known to be the most essential enzyme involved in melanin synthesis.…”
Section: Introductionmentioning
confidence: 99%